Sleep Disturbances in Patients with Nonepileptic Seizures - Vanek J (Dove Medical Press, 2021)
Jakub Vanek,1 Jan Prasko,1– 3 Marie Ociskova,1 Samuel Genzor,4 Michaela Holubova,5 Frantisek Hodny,1 Vlastmil Nesnidal,1 Milos Slepecky,3 Milan Sova,4 Kamila Minarikova1 1Department of Psychiatry, Faculty of Medicine and Dentistry, University Hospital, University Palacky Olomouc, Olomouc, 77520, The Czech Republic; 2Institute for Postgraduate Education in Health Care, Prague, The Czech Republic; 3Department of Psychology Sciences, Faculty of Social Science and Health Care, Constantine the Philosopher University in Nitra, Nitra, The Slovak Republic; 4Department of Respiratory Medicine, University Hospital Olomouc and Faculty of Medicine and Dentistry, Palacky University Olomouc, Olomouc, The Czech Republic; 5Department of Psychiatry, Hospital Liberec, Liberec, The Czech RepublicCorrespondence: Jan PraskoDepartment of Psychiatry, Faculty of Medicine and Dentistry, University Hospital, University Palacky Olomouc, I. P. Pavlova 6, Olomouc, 77900, The Czech RepublicEmail praskojan@seznam.czObjective: Up to 20% of patients treated for epileptic seizures experience psychogenic nonepileptic paroxysms (PNES). These patients present a significant burden for the health care systems because of poor treatment outcomes. The presented review aims to summarize the current state of knowledge on sleep disturbances in patients with nonepileptic seizures.Methods: Articles were acquired via PubMed and Web of Science, and papers between January 1990 and March 2020 were extracted. Inclusion criteria were (1) published in a peer-reviewed journal: (2) studies in humans only; or (3) reviews on a related topic; (4) English language. The exclusion criteria were: (1) abstracts from conferences; (2) commentaries; (3) subjects younger than 18 years. From primary assessment, 122 articles were extracted; after obtaining full texts and secondary articles from reference lists, 45 papers were used in this review.Results: Limited data are available regarding sleep disorders in PNES patients, over the last 30 years only nine original research papers addressed sleep problems in patients with PNES with only six studies assessing objectively measured changes in sleep. Current literature supports the subjective perception of the sleep disturbances with mixed results in objective pathophysiological findings. Conflicting results regarding the REM phase can be found, and studies reported both shortening and prolonging of the REM phase with methodological limitations. Poor sleep quality and shortened duration have been consistently described in most of the studies.Conclusion: Further research on a broader spectrum of patients with PNES is needed, primarily focusing on objective neurophysiological findings. Quality of life in patients suffering from PNES can be increased by good sleep habits and treatment of comorbid sleep disorders.Keywords: psychogenic seizures, sleep disturbances, insomnia, mental disorders, emotional regulation